Overlapping cytokines in H. pylori infection and gastric cancer: A tandem meta-analysis - Yu, Bingting; Xiang, Luochengling; Peppelenbosch, Maikel P.; Fuhler, Gwenny M. (Frontiers in Immunology, 2023)
Background Previous evidence indicated that Helicobacter pylori-induced inflammation is the first step towards gastric carcinogenesis. However, investigations of the immunological factors driving this process have shown inconsistencies. We aimed to present a thorough summary of all researched cytokines in relation to H. pylori infection and GC and relate these to global GC risk. Methods We performed a systematic review and tandem meta-analysis identifying all published studies reporting on serum cytokine levels in H. pylori-infected cases vs. non-infected controls and gastric cancer cases vs. non-gastric cancer controls, with sub-analyses performed to identify global regional differences in cytokine induction and their correlation with GC incidence. Results Only levels of systemic IL-6 (standardized mean difference [SMD]:0.95, 95%CI [0.45;1.45]) and TNF-α (SMD:0.88, 95%CI [0.46; 1.29]) were significantly increased upon H. pylori infection. Sub-analysis showed that of IL-6 levels were increased upon H. pylori infection in East Asian, Middle Eastern and Southeast Asian cohorts, but not in North America, Europe, Russia and Africa. Serum levels of IL-6, IL-7, IL-10, IL-12, and TNF-α were significantly raised in GC. Exploration of the relationship between serum cytokines changes upon H. pylori infection and regional differences in risk of GC development indicated that the SMD of IL-6 serum levels presents a significant correlation with the relative incidence of GC (r=0.81, p=0.00014). Conclusion This study shows that H. pylori infection and GC are associated with increased IL-6 and TNF-α levels. Particularly, IL-6 shows region-specific increases that correlate with GC incidence, making it a key contender for the cause of this disease.